2017
DOI: 10.1021/acs.orglett.7b01402
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conjugate Addition of Electron-Rich Heteroarenes to β,β-Disubstituted Enones

Abstract: Catalytic conjugate additions of heteroarenes to β,β-disubstituted enones are reported. Additions of a range of heteroarene nucleophiles, including furans, indoles, a pyrrole, and a thiophene, to a variety of β,β-disubstituted enones occur to form the corresponding ketone products containing heteroarylated, all-carbon quaternary centers in up to 90% yield. These reactions occur under mild reaction conditions in the presence of low loadings of bismuth triflate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This addition is noteworthy because it results in the formation of a new all‐carbon quaternary center under mild conditions. While indole is known to add to β,β‐disubstituted ketones, we are not aware of any example of indoles reacting with a β,β‐disubstituted ester due to their weaker electrophilicity . Changing the Lewis acid to (C 6 F 5 ) 3 B gave no desired product.…”
Section: Methodsmentioning
confidence: 91%
“…This addition is noteworthy because it results in the formation of a new all‐carbon quaternary center under mild conditions. While indole is known to add to β,β‐disubstituted ketones, we are not aware of any example of indoles reacting with a β,β‐disubstituted ester due to their weaker electrophilicity . Changing the Lewis acid to (C 6 F 5 ) 3 B gave no desired product.…”
Section: Methodsmentioning
confidence: 91%
“…To begin our studies, we chose indole as the nucleophile because indole scaffolds are privileged structural subunits in drug discovery programs, and are present in a large number of biologically active natural products . In addition, indole is fairly non‐basic and is known to react in Lewis acid catalyzed conjugate addition reactions . In our earlier fragmentation and C−H insertion work, we showed that SnCl 4 and (C 6 F 5 ) 3 B were effective Lewis acids and we began our current studies by treating diazo 8 (Scheme ) with SnCl 4 in the presence of indole at −20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The yield of 3aa can be increased to 52–55% when the model reaction is conducted at elevated reaction temperatures (entries 2 and 3). We have previously reported studies that demonstrate nitrogen-containing heteroarenes, including indoles, can inhibit acid catalysts . When the model reaction was run at lower concentrations of indole, product 3aa was generated in 62% yield (entry 4).…”
mentioning
confidence: 99%
“…We sought to develop a complementary strategy to directly incorporate heteroarenes at the C-3 position of steroids containing an α,β-unsaturated ketone. Recently, we reported a bismuth triflate-promoted conjugate addition of electron-rich heteroarenes to β,β-disubstituted enones to construct all-carbon quaternary centers . During studies to assess the scope of these conjugate addition reactions, we found that the conjugate addition of indole to a steroid containing a β,β-disubstituted enone did not occur.…”
mentioning
confidence: 99%